2014
DOI: 10.1097/htr.0b013e3182886d78
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Veteran and Caregiver Knowledge About Mild Traumatic Brain Injury in a VA Medical Center

Abstract: Results of this study may assist in the development of targeted TBI educational interventions for veterans and their friends/family members within the Veterans Affairs system. Ultimately, increased knowledge about mild TBI improves the likelihood that veterans receive care congruent with their needs and may potentially improve outcomes for those with mild TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 42 publications
0
24
0
1
Order By: Relevance
“…While concurrent TBI is a main risk factor for cognitive deficits after SCI, cognitive deficits and TBI do not overlap perfectly, and the discussion of cognitive deficits after SCI is more complicated than presence or absence of TBI. The influence of concurrent TBI on cognition and rehabilitation after SCI is clouded by several factors, including difficulties in accurately identifying cases, as well as misconceptions and misattributions about TBI (Block et al, 2014; Block, West, & Goldin, 2015; McKinlay, Bishop, & McLellan, 2011). Identifying cases for research can be difficult because TBI may not be diagnosed or diagnosed accurately, especially in acute settings.…”
Section: Discussionmentioning
confidence: 99%
“…While concurrent TBI is a main risk factor for cognitive deficits after SCI, cognitive deficits and TBI do not overlap perfectly, and the discussion of cognitive deficits after SCI is more complicated than presence or absence of TBI. The influence of concurrent TBI on cognition and rehabilitation after SCI is clouded by several factors, including difficulties in accurately identifying cases, as well as misconceptions and misattributions about TBI (Block et al, 2014; Block, West, & Goldin, 2015; McKinlay, Bishop, & McLellan, 2011). Identifying cases for research can be difficult because TBI may not be diagnosed or diagnosed accurately, especially in acute settings.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the TBI terms was search in conjunction with each of the other terms (eg, "TBI and knowledge," "TBI and beliefs," "TBI and misconceptions," "TBI and misperceptions") as well as a combination of the other terms (eg, "TBI and knowledge and beliefs") to yield the greatest number of relevant hits. Exclusionary criteria Table 1 A sampling of brain injury misconceptions Wearing seatbelts causes as many brain injuries as it prevents [1,4,6,14,15] Sometimes a second blow to the brain can help a person remember things that were forgotten [1,4,6,14,15] Even when people are in coma for a few weeks, as soon as they wake up, they can recognize and speak to others nearby [1,4,6,14,15] After a brain injury, people can forget who they are and not recognize others, but be normal in every other way [1,4,6,14,15] Emotional problems after brain injury are usually not related to brain damage [1,4,6,14,15] How quickly a person recovers depends mostly on how hard they work at recovering [1,4,6,14,15] Individuals with mild brain injury typically show symptoms that worsen over time [9] Individuals with mild brain injury often require disability [9] Individuals with mild brain injury can forget people they've known for years [9] Individuals with mild brain injury can completely forget who they are [9] included editorials, popular news pieces, and any articles not published in English.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to also consider the impact of the Internet on TBI education. Block et al [9] observed that one-fifth of their sample of veterans and friends/family reported obtaining brain injury information from the Internet. A study of civilian and active duty military nurses [19] indicated that the majority of respondents (80.3% civilian and 84.2% military) endorsed the use of Internet searches to obtain information about mild TBI versus other means, like asking a colleague (73.6%; 78.7%), consulting articles (51.0%; 45.8%), or conferences (37.3%; 22.5%), respectively.…”
Section: Antecedents To Misconceptions: Demographics and Experientialmentioning
confidence: 99%
See 2 more Smart Citations